The Impact of Television News Coverage of Rising and Falling Prices on Food, Gas, and Rent Price Change Expectations in the United States - Fir, Nejc; Dajčman, Silvo; Gajšt, Nataša; Romih, Dejan (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This paper examines whether and how television news coverage of rising and falling prices affects US households’ expectations of food, gas, and rent price changes. Using vector autoregressions and data from June 2013 to October 2024, we find that a sudden and unexpected increase in television news coverage of rising prices on CNN and Fox News leads to a statistically significant decrease in food and gas price change expectations, while the impact on rent price change expectations is statistically insignificant. In contrast, increased television news coverage of falling prices has no statistically significant impact on commodity price change expectations. These findings have important policy implications, as they indicate that the impact of media coverage of rising and falling prices on price change expectations is limited to food and gas, and depends on the content of the news. One possible explanation is that increased media coverage of rising prices signals a tightening of monetary policy, prompting households to revise their short-term price change expectations. To this end, we use the GDELT Project to measure television news coverage, as well as vector autoregression and impulse response analysis.